A Sociological Analysis of The Main Characters in The Novel The Good Earth - Endah Alamsari Andayani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
The purpose of the study is to analyze the main characters by collecting and choosing their actions, speech, and thoughts from the point of view of sociology. The approach is analytical (two methods: an extrinsic approach that deals with theories from some books, sociology ones, and an intrinsic approach that deals with elements in the Buck novel "The Good Earth" itself), characterization that explains the analysis in which the data are theories that support the cycle life of the main characters. Studying in libraries is the method. The writer initially finds that Wang Lung and O-lan's marriage gives them happiness. They rise from a position of poverty to one of wealth. By the time the story comes to an ends, the key main characters have all passed away and have all come back to earth. The condition of the earth determines Wang Lung's fate throughout his entire existence, which is an ongoing struggle against the twin spectres of famine and destruction.These facts drive the writer to investigate both their characteristics and how they interact with society as newly wealthy individuals. The conclusion shows that as humans originated from the earth, we will also return to it after death.